The Arabic Concept of Dīn and Islamic Religious Sciences in the 18th Century: The Case of Murtaḍā al-Zabīdī (d. 1791) - Reichmuth, Stefan (Oriens, 2016)
The Arabic word dīn, the central concept of “Religion” in Islam, has a long and complex history which reflected the interreligious landscape of the Middle East. This included a universal notion pertaining to all kinds of worship, sacred order and personal ‘religiosity’, with Islam as their final and most perfect form. The case study of the lexicographer and Sufi theologian Murtaḍā al-Zabīdī (d. 1205/1791) reviews his lexicographical approach to dīn with his significant additions from later usage. His attempts at merging mystical and empirical knowledge in the universal realm of dīn in a post-Ġazzālian framework are also discussed.